Origins and Neurochemical Complexity of Preganglionic Neurons Supplying the Superior Cervical Ganglion in the Domestic Pig - Juranek, Judyta K. (J Mol Neurosci, 2014)
The superior cervical ganglion (SCG) is a center of sympathetic innervation of all head and neck organs. SCG sympathetic preganglionic neurons (SPN) were found in the nucleus intermediolateralis pars principalis (IMLpp), the nucleus intermediolateralis pars funicularis (IMLpf), the nucleus intercalatus spinalis (IC), and the nucleus intercalatus spinalis pars paraependymalis (ICpe). Despite its importance, little is known of SCG innervation and chemical coding in the laboratory pig, a model that is physiologically and anatomically representative of humans. Here in our study, we established the distribution and chemical coding of Fast Blue (FB) retrogradely labelled SPN innervating porcine SCG. After unilateral injection of FB retrograde tracer into the left SCG, labeled neurons were found solely on the ipsilateral side with approximately 98 % located in Th(1)–Th(3) segments and predominantly distributed in the IMLpp and IMLpf. Neurochemical analysis revealed that approximately 80 % of SPN were positive both to choline acetyltransferase (ChAT) and nitric oxide synthase (NOS) and were surrounded by a plethora of opioidergic and peptiergic nerve terminals. The results of our study provide a detailed description of the porcine preganglionic neuroarchitecture of neurons controlling the SCG, setting the stage for further studies concerning SPN plasticity under experimental/pathological conditions.